Realising resolution 275 to combat homophobic rape of LBQ+ women as a conversion practice in Namibia - Sogunro, Ayodele (University of Pretoria, 2024)
Mini Dissertation (LLM (Sexual and Reproductive Rights in Africa))--University of Pretoria, 2023.